Pengaruh Rasio CAEL Terhadap Kinerja Keuangan Bank Yang Terdaftar Di PT. BEI - dewi, sandra; Sudiartha, Gede Merta (E-Jurnal Manajemen; Vol 1 No 2 (2012), 2012)
In this study, using statistical regression tool. Regression was used is the classical assumption test, linear regression, F-test and T-test. Sampling study using purposive sampling method, the sample of 20 banking companies in accordance with the criteria ditentukan.Berdasarkan results of 20 banks, it is known that simultaneous variable capital, assets, earnings, and liquidity siagnifikan affect the financial performance of the bank 0.004 significance level less than 0.005. From the partial calculation using T test (T-test) result that assets and earnings variables significantly affect the financial performance of the bank's significance is smaller than 2.5%, while capital and liquidity variable does not affect the bank's financial performance to the level of significance larger 2.5%.
Keywords: asstes, capital, earnings, , financial performance, dan liquidity